Analysis of a Trigeneration Plant under Transient Operating Conditions. (August 2018) - Perrone, D.; Morrone, P.; Castiglione, T.; Algieri, A.; Bova, S.
Abstract: A dynamic lumped-parameters model has been developed in order to analyse the performance of a combined cooling, heating and power (CCHP) plant during transient load variations. The plant allows the waste heat recovery from four Internal Combustion Engines (ICEs) to produce simultaneously refrigeration power for an absorption chiller, hot water for thermal user and electrical power. The heat recovery is realized through the exhaust gases, the jacket cooling water and the lubricant. The plant includes an auxiliary boiler, which maintains the water temperature levels to the values required by the absorption chiller, and a dry-cooler, which refrigerates the plant water before entering the internal combustion engines. Moreover, a three-way valve, which controls the water flow rate in order to satisfy both the refrigeration and the thermal loads, is considered. The simulations are carried out under thermal-drive and electric-drive strategy and the evaluation of the performance and time response of the CCHP apparatus are presented.